(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Abstract Purpose: This study investigates the challenges encountered by library professionals during the computerization of college libraries in Western Vidarbha, India. Methodology: A descriptive survey was conducted across 151 NAAC-accredited college libraries affiliated with Sant Gadge Baba Amravati University. Findings: While core services such as OPAC (98.68%) and Circulation (86.09%) are highly computerized, administrative services like Acquisition (60.93% not computerized) and Inter-library Loans (73.51%) remain underdeveloped. Barriers include the lack of user-friendly LMS, shortage of trained staff, and inadequate manpower. Implications: These issues hinder the transformation of college libraries into fully automated information centers. Originality: This study adds value by focusing on challenges in resource-constrained, semi-rural regions of India, offering data-driven strategies to bridge automation gaps.